PARADIGMS IN CONSUMER BEHAVIOR - Sihombing, Sabrina Oktoria (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
A paradigm influences what we see and conceive about certain facts. Paradigm can also influence what we accept as a truth. Yet, the debate over which paradigm and methodology is best suit for marketing and consumer behavior has begun since 1980s. Many researchers criticized the domination of logical empiricism paradigm and offered alternative paradigm to understand marketing and consumer behavior. This article discusses several paradigms and methodology, which are part of qualitative paradigm, and compares them with positivism paradigm. This article will also point to the importance of reconciliation between qualitative and quantitative paradigm in order to improve marketing and consumer behavior studies.